Ministry Of Finance Decree No. 426 of the Year 2022 Amending Certain Provisions of teh Executive Regulations of the Value Added Tax Law No. 67 of the Year 2016 = وزارة المالية قرار رقم 426 لسنة 2022 بتعديل بعض أحكام اللائحة التنفيذية لقانون الضريبة على القيمة المضافة الصادر بالقانون رقم 67 لسنة 2016 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic